The bookplates of the fund of Lituanica of the 18th century at the library of Lithuanian academy of science - Alma Braziūnienė (Knygotyra)
This article is the sequel to the article "The Bookplates of the Fund of Lituanica of the 17th Century at the Library of Lithuanian Academy of Science."